Felt : Fluxus, Joseph Beuys, and the Dalai Lama - Thompson, Chris (University of Minnesota Press, 2011)
This title provides a non-linear look at the engagement of the postwar avant-garde with Eastern spirituality, a context in which the German artist Joseph Beuys appears as an uneasy shaman. Centred on a highly publicised yet famously inconclusive 1982 meeting between Beuys and the Dalai Lama, arranged by the Dutch artist Louwrien Wijers, this book explores the interconnections among Beuys, the Fluxus movement, and Eastern philosophy and spiritual practice.